GREEN MARKETING AND ITS IMPLICATIONS - Marthin Nanere (UPT Penerbitan Universitas Jember, 2012)
The concept of green marketing is defined as organisation’s efforts at designing,promoting, pricing and distributing products that will not harm the environment. Clearly,there are many considerations that may be addressed by businesses that choose toundertake a green marketing agenda. To align themselves with the green initiatives,businesses often focus on one or more of the three cornerstones of the green marketingstrategy called the 3-Rs: reusing, recycling and reducing. These practices are aimed atcontrolling the amount of natural resources waste that often accompanies firms’ marketingactivities. By reusing of promotional materials, recycling materials (e.g. using recycledpapers to make bags) and reducing resource usage (e.g. energy conservation, sharing ofcomputers and transportation facilities), business or organisation can play a significant rolein protecting the environment. For services, reducing would include reworking serviceprocesses to reduce their impact on the environment. Such practices may also help positionspecific businesses or organisations as green oriented in the public’s mind and attract theincreasingly large green consumer segment.